2016
DOI: 10.1021/acsphotonics.6b00246
|View full text |Cite
|
Sign up to set email alerts
|

Multicolor Changeable Optical Coating by Adopting Multiple Layers of Ultrathin Phase Change Material Film

Abstract: The multilayered optical coating whose structure consists of optical cavity and multiple layers of ultrathin phase change material (PCM) film is presented. The color changing is enabled via transition between amorphous and crystalline phases of PCM, which is accompanied by high optical contrast. The phase transition of each PCM layer, separated by ultrathin oxide barrier, can be realized through various crystallization temperatures with respect to the different thickness of ultrathin (<10 nm) PCM film. Accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
68
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(75 citation statements)
references
References 21 publications
1
68
0
Order By: Relevance
“…Only two colours can be tuned via the full crystallization of the few-nanometres-thick GST layer without the contribution provided by changing the thickness of indium tin oxide (ITO) beneath the GST. Previous studies tend to use single phase change material (PCM) as a highly absorbing dielectric layer to realize colour depth modulation, for example, Ag 3 In 4 Sb 76 Te 17 (AIST)9 and two ultrathin GST films10. However, the method based on two ultrathin GST films needs a barrier layer to avoid interdiffusion, which will adversely interfere with the amorphization during actual device operation10 and is unstable because it need accurate thickness control.…”
mentioning
confidence: 99%
“…Only two colours can be tuned via the full crystallization of the few-nanometres-thick GST layer without the contribution provided by changing the thickness of indium tin oxide (ITO) beneath the GST. Previous studies tend to use single phase change material (PCM) as a highly absorbing dielectric layer to realize colour depth modulation, for example, Ag 3 In 4 Sb 76 Te 17 (AIST)9 and two ultrathin GST films10. However, the method based on two ultrathin GST films needs a barrier layer to avoid interdiffusion, which will adversely interfere with the amorphization during actual device operation10 and is unstable because it need accurate thickness control.…”
mentioning
confidence: 99%
“…Such a thermal barrier layer keeps surrounding materials isolated from heating and protects them from harmful interaction with the GST film, when GST is switched between its two phases by optically, electrically or thermally provided heat stimuli [35,40,45]. For example, Ta 2 O 5 , Al 2 O 3 and Si 3 N 4 are materials which can be chosen for the thermal barrier due to their low thermal conductivities [35,40,45]. We found that the addition of such a thin thermal barrier layer does not affect the functionality of the proposed structure.…”
Section: Discussionmentioning
confidence: 99%
“…2(d) and 2(f)]. Note that the bulk refractive index of GST that we used here is still valid for the ultrathin GST layer with 2 nm thickness [40,45].…”
Section: Switching Of the Direction Of Reflectionless Light Propagationmentioning
confidence: 99%
See 1 more Smart Citation
“…Through the study of a nanolayer stack, we show that using a 4π configuration [9] to Raman microscopy has a great potential to help in this quest. Nanolayers have attracted increasing interest across a wide diversity of fields, such as optics [10], energy storage [11], biology [12], and pharmacology [13]. They are typically characterized via ellipsometry, electron microscopy, or x-rays; however, these techniques share a common limitation: data from complex stacks of nanolayers become increasingly difficult to interpret.…”
mentioning
confidence: 99%